2000
DOI: 10.1007/s007750000113
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the chemical and biological properties of trans platinum complexes: monofunctional platinum complexes containing one nucleobase as potential antiviral chemotypes

Abstract: Replacement of one of the chloride leaving groups in trans-[PtCl2(NH3)(L)] by the nucleobase 9-ethylguanine gives the nucleobase cations [SP-4-2]-[PtCl(9-ethylguanine)(NH3)(L)]+ (L = NH3, 1; L = quinoline, 3), which are models for the monofunctional adduct on DNA. Displacement of Cl- in 1 and 3 by either 5'-guanosine monophosphate (5'-GMP) or N-acetyl-L-methionine (N-AcMet) showed clear kinetic preference for the sulfur (estimated half-lives of 1.5 and 4 h with N-AcMet against 7 and 17 h for 5'-GMP for 1 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 22 publications
1
30
0
1
Order By: Relevance
“…Clearly the issues of both protein selectivity and consequently cellular selectivity (cytotoxicity versus inhibition of viral infectivity) are critical parameters in development of agents with useful antiviral activity. In this respect, it is axiomatic that the zinc finger modifications observed here are likely to lead to loss of protein function, as suggested previously [5,6]. The fact that [AuCl(dien)] + is cytotoxic whereas [PtCl(dien)] + is not suggests that systematic studies of metal complexes with new targets (e.g.…”
Section: Biological Relevancementioning
confidence: 76%
See 1 more Smart Citation
“…Clearly the issues of both protein selectivity and consequently cellular selectivity (cytotoxicity versus inhibition of viral infectivity) are critical parameters in development of agents with useful antiviral activity. In this respect, it is axiomatic that the zinc finger modifications observed here are likely to lead to loss of protein function, as suggested previously [5,6]. The fact that [AuCl(dien)] + is cytotoxic whereas [PtCl(dien)] + is not suggests that systematic studies of metal complexes with new targets (e.g.…”
Section: Biological Relevancementioning
confidence: 76%
“…Such chemistry may be implicated in the antiviral activity of this class of compounds [6]. Finally, novel mechanisms of action of medicinal inorganic compounds have been proposed based on the interaction with diverse zinc finger proteins of aurothiomalate [7] and most recently antimonates [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is of interest to briefly compare in vitro inhibition of infectivity of the prototype [Pt(dien)(9-EtGua)] 2+ with the compound SP -4-2-[PtCl(NH 3 )(9-EtGua)(quinoline)] + which displayed modest anti-HIV activity. 55 For comparison, exploratory activity of [Pt(dien)(9-EtGua)] 2+ against HIV-1 strains BaL, NL4-3 and 91-US001 strains in peripheral mononuclear blood (PBMC) cells showed only modest HIV inhibitory activity for the latter with an IC 50 = 28.61 μM (Roger Ptak, personal communication). A number of extra factors come into play when considering cellular properties – amongst them the overall stability of the complex in blood and other non-selective interactions.…”
Section: Discussionmentioning
confidence: 99%
“…We used PAR to qualitatively demonstrate zinc ejection from this CCHC nucleocapsid zinc finger as previously reported . PAR is a tridentate ligand forming ML 2 ‐type complexes with Zn(II) and other transition metals and is used to measure micromolar concentrations of these metals .…”
Section: Resultsmentioning
confidence: 98%
“…These authors demonstrated that, upon binding to cisplatin, CCCC and CCHC zinc finger domains release zinc ions, undergoing dramatic structural modifications. Other studies have shown that trans ‐platinum derivatives are capable of ejecting zinc ion from a CCHC‐type zinc finger domain of the HIV‐1 nucleocapsid protein (NCp7) and exerting antiretroviral activity . It is worth noting that CCHC zinc binding domains with very high amino acid sequence and functional homology to corresponding domains of retroviral nucleocapsid proteins are present in CNBPs, also known as CCHC‐type zinc finger CNBPs .…”
Section: Introductionmentioning
confidence: 99%